EEstimating children's weight in the emergency department using a length-based, habitus-modified system to increase the accuracy of total body weight estimation: the utility of the PAWPER tape in paediatric emergency medicine ta - Wells, Mike (My University, 2018)
An accurate estimation of weight during the management of medical emergencies in children is essential to permit effective intervention and to avoid medication errors. Although older methods of weight estimation, such as age-based formulas and the Broselow tape, are still being used, they have failed to achieve an acceptable standard of accuracy. The newer, dual length- and habitus-based systems, such as the PAWPER tape system, have been evaluated in a wide variety of populations and shown to be significantly more accurate. However, some limitations in the PAWPER system have been identified including the subjectivity of habitus assessment and a relatively lower weight estimation accuracy in very obese children. The increasing prevalence of severe obesity in both first and third world countries requires a strategy to mitigate the increased risk of poor outcomes from drug dosing errors in obese children. This requires an increased sophistication from weight estimation systems as both total body weight and ideal body weight are required for appropriate drug dosing. The series of studies that make up this thesis was designed to develop an evidence base from which to refine and validate the second version of the PAWPER tape (the PAWPER XL tape). It was also intended to further clarify its optimum design as the imperative for accurate and appropriate weight estimation cannot be ignored. Since any increased complexity in weight estimation methodology may lead to heightened risk of errors, the upgraded PAWPER XL system was specifically formulated to minimise the potential for errors through developing cognitively neutral weight estimation processes, embracing technological adjuvants and advocating for adequate and appropriate training in weight estimation techniques.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2018
Keywords: Child nutrition disorders; Child development; Paediatrics